Modified Peptide YY Molecule Attenuates the Activity of NPY/AgRP Neurons and Reduces Food Intake in Male Mice - Jones, Edward S (Endocrinology, 2019)
To study the effects of an analog of the gut-produced hormone peptide YY (PYY(3-36)), which has increased selectivity for the Y2 receptor; specifically, to record its effects on food intake and on hypothalamic neuropeptide Y/agouti-related peptide (NPY/AgRP) neuron activity. NNC0165-1273, a modified form of the peptide hormone PYY(3-36) with potent selectivity at Y2 receptor (>5000-fold over Y1, 1250-fold over Y4, and 650-fold over Y5 receptor), was tested in vivo and in vitro in mouse models. NNC0165-1273 has fivefold lower relative affinity for Y2 compared with PYY(3-36), but >250-, 192-, and 400-fold higher selectivity, respectively, for the Y1, Y4, and Y5 receptors. NNC0165-1273 produced a reduction in nighttime feeding at a dose at which PYY(3-36) loses efficacy. The normal behavioral satiety sequence observed suggests that NNC0165-1273 is not nauseating and, instead, reduces food intake by producing early satiety. Additionally, NNC0165-1273 blocked ghrelin-induced cFos expression in NPY/AgRP neurons. In vitro electrophysiological recordings showed that, opposite to ghrelin, NNC0165-1273 hyperpolarized NPY/AgRP neurons and reduced action potential frequency. Administration of NNC0165-1273 via subcutaneous osmotic minipump caused a dose-dependent decrease in body weight and fat mass in an obese mouse model. Finally, NNC0165-1273 attenuated the feeding response when NPY/AgRP neurons were activated using ghrelin or more selectively with designer receptors. NNC0165-1273 is nonnauseating and stimulates a satiety response through, at least in part, a direct action on hypothalamic NPY/AgRP neurons. Modification of PYY(3-36) to produce compounds with increased affinity to Y2 receptors may be useful as antiobesity therapies in humans.